Emotional responses of Korean and Chinese women to Hangul phonemes to the gender of an artificial intelligence voice - Lee, Min-Sun; Lee, Gi-Eun; Lee, San Ho; Lee, Jang-Han (Frontiers in Psychology, 2024)
The purpose of this study was to explore the arousal and valence that people feel in relation to Hangeul phonemes according to the gender of an AI speaker through comparison with other cultures. For this purpose, 42 Hangeul phonemes were used in a combination of 3 Korean vowels and 14 Korean consonants to explore cultural differences in arousal, valence, and basic 6 emotions according to the gender of an AI speaker. A total of 136 Korean and Chinese women were recruited and randomly assigned to one of two conditions in a 2 (voice gender: female or male). This study revealed that Korean and Chinese women showed remarkable differences in arousal for male voices, and Chinese women in particular showed clear differences in emotional perceptions of male and female voices in response to voiced consonants. These results confirm that arousal and valence may differ in articulation types and vowels depending on cultural differences and that voice gender can also affect perceived emotions. This principle can be used as evidence for sound symbolism and has practical implications for voice gender and branding in AI applications.